2018
DOI: 10.5603/fm.a2018.0011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dimensions of pneumatisation of the anterior clinoid process in middle Anatolian population by computed tomography

Abstract: Radiologically recognising pneumatisation and anatomical variations of the ACP may be helpful in decreasing the incidence of surgical complications during anterior clinoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 8 publications
(14 reference statements)
7
8
1
Order By: Relevance
“…Our incidence rates were found compatible with the incidence ranges (70.5%-87.7% for without ACP pneumatization, 6.6%-14% for Type 1, 3.4%-12% for Type 2, and 2%-4% for Type 3) in the literature (Supplementary Table 11, Supplemental Digital Content 11, http:// links.lww.com/SCS/E322). 25,33,50 We observed that ACP length, width, and angle increased depending on pneumatization, similar to Sabanciogullari et al, 39 who stated that the basal width in ACPs with pneumatization was greater than without pneumatization. Our findings showed that the incidence of ACP pneumatization was affected by sex differences (P < 0.001), but not sides (P = 0.931).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our incidence rates were found compatible with the incidence ranges (70.5%-87.7% for without ACP pneumatization, 6.6%-14% for Type 1, 3.4%-12% for Type 2, and 2%-4% for Type 3) in the literature (Supplementary Table 11, Supplemental Digital Content 11, http:// links.lww.com/SCS/E322). 25,33,50 We observed that ACP length, width, and angle increased depending on pneumatization, similar to Sabanciogullari et al, 39 who stated that the basal width in ACPs with pneumatization was greater than without pneumatization. Our findings showed that the incidence of ACP pneumatization was affected by sex differences (P < 0.001), but not sides (P = 0.931).…”
Section: Discussionsupporting
confidence: 87%
“…13,19,23,32,39,42 For example, Cecen et al 23 observed that the mean length and width of ACP on dry skulls were statistically smaller than that on computed tomography. In this study, Dis-ACP-OS, ACP length, width and angle were found as greater in males than in females, similar to Sabanciogullari et al 39 (who showed that the length and width in males was greater compared with females). However, Beger et al 19 did not observe significant differences according to sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11. Anterior clinoid process length (ACPL); (ACPL-R) for right side and (ACPL-L) for left side: The height from the apex of anterior clinoid to the medial margin of the optic canal on the same side (Sabanciogullari et al, 2018).…”
Section: Posterior Clinoid Distance (Pcd)mentioning
confidence: 99%
“…On the other hand; Islam et al (2017) in Bangladeshi population and Hasan et al (2016b) in Iraqi population; reported non-significant difference between males and females as regard Sella measures. Moreover; few non-Egyptian studies concerned with sex related differences of anterior and posterior clinoid processes dimensions as well as distances between them (Sakran et al, 2015;Sabanciogullari et al, 2018;Chou et al, 2021Chou et al, , 2022.…”
Section: Introduction mentioning
confidence: 99%